HUKUM MODERN - Harsana; Rezki Adriyan; Frengki Andika; Ayranda Eka Putra (STKIP Subang, 2024)
Modern law, as a legal system that governs relationships between individuals, states, and the international community, has evolved in response to the social, economic, and technological dynamics of globalization. This study aims to analyze the implementation of modern law in addressing the challenges of globalization, social change, and technological development. Through a qualitative approach and descriptive analysis, this research explores how modern law is applied in various countries and its adaptation to contemporary issues such as human rights, transnational crime, and climate change. The findings indicate that, while modern law provides a more structured and formal framework for resolving both international and domestic conflicts, significant challenges arise in its implementation and alignment with traditional legal systems, local cultures, and the rapid pace of technological development. Therefore, the study recommends the need for more responsive and flexible legal reforms, as well as enhanced international collaboration to address the global issues that continue to evolve.